Directed Reading Thinking Activity (DRTA) Method and Students' Critical Thinking Level in Editing Scientific Articles - Asep Supriyana; Emzir Emzir; Endry Boeriswati (BAHASTRA, 2019)
The aim of this research is to explain the use of the DRTA method and the level of critical thinking in improving students' ability in editing scientific articles. The method used in this research is experimental research. The result shows that using the DRTA method affected the ability to edit scientific articles if it is in accordance to the students’ level of critical thinking (high and low). Learning outcomes of editing scientific articles of students who have high critical thinking scales are different from learning outcomes of editing scientific articles of students who have low level of critical thinking. Students who were treated with the DRTA Method had higher level of critical thinking and had significant differences from those who had low levels of critical thinking. The acquisition of the average score showed the students who studied with the DRTA method and had a high critical thinking level are 90.1, while the score of the students who had a low critical thinking level are 79.3.